Design, synthesis and evaluation of novel cinnamic acid derivatives bearing N-benzyl pyridinium moiety as multifunctional cholinesterase inhibitors for Alzheimer’s disease - Lan, Jin-Shuai (J Enzyme Inhib Med Chem, 2017)
A novel family of cinnamic acid derivatives has been developed to be multifunctional cholinesterase inhibitors against AD by fusing N-benzyl pyridinium moiety and different substituted cinnamic acids. In vitro studies showed that most compounds were endowed with a noteworthy ability to inhibit cholinesterase, self-induced Aβ (1–42) aggregation, and to chelate metal ions. Especially, compound 5l showed potent cholinesterase inhibitory activity (IC(50), 12.1 nM for eeAChE, 8.6 nM for hAChE, 2.6 μM for eqBuChE and 4.4 μM for hBuChE) and the highest selectivity toward AChE over BuChE. It also showed good inhibition of Aβ (1–42) aggregation (64.7% at 20 μM) and good neuroprotection on PC12 cells against amyloid-induced cell toxicity. Finally, compound 5l could penetrate the BBB, as forecasted by the PAMPA-BBB assay and proved in OF1 mice by ex vivo experiments. Overall, compound 5l seems to be a promising lead compound for the treatment of Alzheimer’s diseases.